2020
DOI: 10.1111/jocs.15112
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of arch vessels: Imaging characteristics and associations on multidetector computed tomography angiography

Abstract: Aim: To evaluate the imaging characteristics and associations in patients with isolation of arch vessels on multidetector computed tomography angiography (CTA). Materials and Methods: We retrospectively reviewed all multidetector CTA studies performed for the evaluation of congenital heart diseases (CHDs) at our institution from January 2014 to June 2020. Cases with isolation of arch vessels were identified. The isolated arch artery and its relationship with patent arterial duct, pulmonary artery, and aortic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…IABA is commonly associated with other intra-cardiac CHDs and chromosome abnormalities. Sinha et al reported that 57.1% (8/14) cases of ILSCA were combined with TOF, the most common intra-cardiac anomaly (4), which agrees with our results. Luetmer et al (3) reported that 59% (23/39) of cases with ILSCA were combined with CHD and TOF, accounting for 60.87% (13/24) of cases.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…IABA is commonly associated with other intra-cardiac CHDs and chromosome abnormalities. Sinha et al reported that 57.1% (8/14) cases of ILSCA were combined with TOF, the most common intra-cardiac anomaly (4), which agrees with our results. Luetmer et al (3) reported that 59% (23/39) of cases with ILSCA were combined with CHD and TOF, accounting for 60.87% (13/24) of cases.…”
Section: Discussionsupporting
confidence: 93%
“…The ILSCA and IRSCA were reported by Barger et al in 1956 (15) and 1954 (16), respectively, while the first cases of ILIA were described by Levine et al in 1966 (17). The detection rate of the IABA in the cases of CHD was 0.15%, while Sinha et al reported that the prevalence of the IABA in the CHD population was 0.36% in a single center after birth (4). There may be two reasons for this: (i) some cases may be misdiagnosed due to a lack of awareness of IABA; and (ii) more cases with CHD were diagnosed prenatally, and some cases, which could have a more severe prognosis in comparison to cases with CHD that survive after birth, may be terminated pregnancies or die at an early age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations